Spatial genetic structure of the invasive tree Robinia pseudoacacia to determine migration patterns to inform best practices for riparian restoration. Issue 5 (24th August 2020) - Yaegashi, Sakiko; Omura, Tatsuo; Watanabe, Kozo
Abstract: The black locust Robinia pseudoacacia (Robinieae, Fabaceae) is a common invasive riparian tree in Japan. There are less effective management strategies to remove the tree from the riparian area because of its quickly established high population. We investigated the expansion patterns of R. pseudoacacia through sympatric (i.e. between high- and low-water channel (HWC/LWC) within a study site) and allopatric (i.e. along river corridor) dispersal in the Tama River (Tokyo, Japan). Four microsatellites were used to examine the effects of gene flow on six populations in three sites. These subpopulations showed small genetic distance (i.e. no barrier or slightly limited) and genetically mixed population structure. It indicated that both sympatric and allopatric dispersals were active. Many migrants were younger individuals (i.e. <5 years old) and were found in the LWC area. Thus, the LWC could receive more migrants than the HWC through both types of dispersals. In addition, our age and genetic structure analyses reveal that recruited individuals likely settled immediately after the clearing project of R. pseudoacacia through sympatric dispersal. It appears that the migration by allopatric dispersal occurred following this. For the effective management of R. pseudoacacia, migrants should be removed regularly following initial removal of invaders during site restoration. Abstract : The black locust Robinia pseudoacacia is a common invasive species inhabiting Japanese river banks. It is problematic both for ecosystem and disaster prevention. We investigated the expansion strategy of the tree based on gene flow on three sites, in Tama River using microsatellites. A clearing project was conducted on a site. Migrants seemed to be settled immediately on the riverside after the clearing project from the close population first, and then river water could carry new migrants. For the plant's effective management, migrants should be removed regularly following the initial removal of invaders during site restoration.